Analisa persepsi penerima program BSPS Nagari Bungo Pasang Salido Kecamatan IV Jurai Kabupaten Pesisir Selatan - Dian Wahyoni DF; Merry Thressia; Mulyadi Mulyadi (Jurnal Zona, 2021)
The state is responsible for protecting the entire Indonesian nation through the implementation of housing and settlement areas so that people are able to live and occupy decent and affordable houses in a healthy, safe, harmonious and sustainable environment throughout Indonesia. Implementation of Self-Help Housing Stimulant Assistance (BSPS) is carried out through activities to improve the quality of self-help houses and the construction of new self-help houses as well as incentives for the construction of new self-help houses in the form of infrastructure, facilities and public utilities. One of the areas targeted by the BSPS program is Nagari Bungo Pasang Salido. This study aims to 1). evaluate the results of the implementation of the BSPS Program and see the results of its achievements in terms of security and standard housing structures for beneficiaries, 2). improve the quality of basic research results and produce scientific publications in reputable international scientific journals. This research uses the direct method by distributing questionnaires to the recipients of the BSPS program assistance. The results of this research show that the study of the achievement of the BSPS program for the beneficiary community is very good, with a questionnaire result with a percentage of 100%. The study on the safety of beneficiaries in occupying a house that is suitable for habitation with the feasibility of a fairly good structure, where the average percentage is 76.5% consisting of 7 indicators with 6 indicators worth 100% and 1 indicator worth 35.7%. The results of the Achievement of the Standards for Habitable House Structures for the BSPS Program in Structure Development, the average result is 97.19% consisting of 14 indicators.